Teoría de la mente en niños preescolares: diferencias entre sexos y capacidad de memoria de trabajo - Padilla Mora, Michael (2009)
Theory of mind refers to the ability to predict and explain the behaviour of others in terms of their internal mental states, and has been recognized as a fundamental aspect of the cognitive development during the preschool years. On the other hand, the working memory capacity is a memory system that allows us to keep in mind certain number of representations simultaneously, and has been also considered as a central ability for the preschool population cognitive development. The present research analyzes the relation amid theory of mind development and working memory capacity in a sample of 60 preschool children from 5 to 7 years of age, making special emphasis in the identification of possible differences between both sexes. The assessment of theory of mind development implied the administration of 6 false belief tasks, and the working memory capacity was assessed through 2 different self-ordered pointing tasks. The results show differences in theory of mind development between boys and girls, and gave no evidence of associations between theory of mind development and working memory capacity. These findings are discussed in the context of the actual debate on theory of mind development and sex differences in cognitive development.